The The Influence of Leadership Style and Work Environment on Employee Performance at PT Bank Arta Kedaton, Bandar Lampun - Bill leonardo; Hamartoni Ahadis (Economics and Digital Business Review, 2026)
This study was conducted at PT Bank Arta Kedaton to examine the extent to which leadership style and work environment influence employee performance effectiveness. The research employed a quantitative method, with data collected through questionnaires. The findings revealed that leadership style has a significant influence in enhancing employee productivity. Meanwhile, the work environment also contributes positively to work efficiency. Further statistical analysis indicated that the work environment tends to have a greater influence compared to leadership style. Several aspects, such as the availability of facilities, strong interpersonal relationships, and comfortable working conditions, play an important role in improving employee motivation and work outcomes. Therefore, the strategic recommendation for the company is to optimize visionary leadership styles and establish an ergonomic and collaborative work environment in order to achieve better business objectives.